2009
DOI: 10.3899/jrheum.080855
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic Risks of Anti-Cyclical Citrullinated Peptide Antibodies in a North American Native Population with Rheumatoid Arthritis and Their First-degree Relatives

Abstract: An independent association of the non-SE allele DRB1*0901 with RA was confirmed in this population, and this allele in combination with a SE allele was associated with younger age at disease onset. FDR of RA probands have a higher prevalence of anti-CCP antibodies than more distant relatives and unrelated controls, suggesting a gradient of risk for disease development. Immunogenetic risks may act early in disease pathogenesis at the level of initiation of RA autoantibody formation; however, it is not clear wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 23 publications
9
70
0
1
Order By: Relevance
“…4 Moreover, as is the case with a number of the NAN populations that have been studied, we have shown that the Cree/Ojibway population in Central Canada has a high prevalence of SE alleles, specifically *0404 and *1402. 8 Because of the high prevalence of SE in the population, we looked for SNP associations in non-HLA regions that may further predispose NAN individuals to RA, or alternatively, protect them from the risk associated with SE. In the current study, we show that several non-HLA SNP were marginally associated with RA risk in the NAN population, but that SNPs in the TRAF1-C5 and MMEL1-TNFRSF14 regions interacted significantly with SE, albeit in opposite directions with the former increasing risk and the latter being protective in the presence of the HLA-DRB1 risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Moreover, as is the case with a number of the NAN populations that have been studied, we have shown that the Cree/Ojibway population in Central Canada has a high prevalence of SE alleles, specifically *0404 and *1402. 8 Because of the high prevalence of SE in the population, we looked for SNP associations in non-HLA regions that may further predispose NAN individuals to RA, or alternatively, protect them from the risk associated with SE. In the current study, we show that several non-HLA SNP were marginally associated with RA risk in the NAN population, but that SNPs in the TRAF1-C5 and MMEL1-TNFRSF14 regions interacted significantly with SE, albeit in opposite directions with the former increasing risk and the latter being protective in the presence of the HLA-DRB1 risk.…”
Section: Discussionmentioning
confidence: 99%
“…8 The following DRB1 alleles were included as SE-bearing alleles: DRB1*0101, 0102, 0401, 0404, 0405, 0408, 0410, 1001 and 1402. Other SE-bearing alleles were not found in this population.…”
Section: Study Subjectsmentioning
confidence: 99%
See 3 more Smart Citations